Recent advances of the nanocomposite hydrogel as a local drug delivery for diabetic ulcers - Tong, Sen; Li, Qingyu; Liu, Qiaoyan; Song, Bo; Wu, Junzi (Frontiers in Bioengineering and Biotechnology, 2022)
Diabetic ulcer is a serious complication of diabetes. Compared with that of healthy people, the skin of patients with a diabetic ulcer is more easily damaged and difficult to heal. Without early intervention, the disease will become increasingly serious, often leading to amputation or even death. Most current treatment methods cannot achieve a good wound healing effect. Numerous studies have shown that a nanocomposite hydrogel serves as an ideal drug delivery method to promote the healing of a diabetic ulcer because of its better drug loading capacity and stability. Nanocomposite hydrogels can be loaded with one or more drugs for application to chronic ulcer wounds to promote rapid wound healing. Therefore, this paper reviews the latest progress of delivery systems based on nanocomposite hydrogels in promoting diabetic ulcer healing. Through a review of the recent literature, we put forward the shortcomings and improvement strategies of nanocomposite hydrogels in the treatment of diabetic ulcers.